Struktura normatywna przepisu karnego - Wróbel, Włodzimierz (Wydział Prawa i Administracji UAM, 1993)
The author analyses different conceptions concerning a model structure of a provision of the criminal law and the way those elements are reflected in the statute. The analysis is carried out from the point of view of t he adequacy of those conceptions for the application of the criminal law.
Normative structure of aprovision of the criminal law